Prevalence of Extrapyramidal Symptoms in In-Patients With Severe Mental Illnesses: Focus on Parkinsonism - Roiter, Beatrice; Pigato, Giorgio; Antonini, Angelo (Frontiers in Neurology, 2020)
Patients with severe mental illnesses may present extrapyramidal symptoms as part of a concomitant neurological disorder or secondary to medications. Extrapyramidal symptoms are frequently unrecognized, have negative consequences for adherence to treatment, negatively affect quality of life and can induce stigma. We estimated and correlated with demographic and clinical variables prevalence of extrapyramidal symptoms in in-patients with severe mental illnesses. Additionally we evaluated 123I-FP-CIT SPECT binding to striatal dopamine transporter in subjects with clinical manifestations suggestive of Parkinson’s Disease and recorded therapeutic management and clinical evolution for 6-months. Extrapyramidal symptoms were present in 144 out of 285 patients (50.5%), mainly tremor (94 patients, 33%). There were 38 patients (13.3%) with parkinsonism and they had older age, more medical comorbidities and medical treatments. In 15/38 patients striatal dopamine transporter binding was abnormal resulting in dose reduction or change of psychotropic drugs as well as combination with antiparkinson therapy. Our study confirmed the clinical and epidemiological relevance of extrapyramidal symptoms among inpatients with severe mental illnesses. A small percentage of patients with extrapyramidal symptoms had features compatible with possible diagnosis of Parkinson’s Disease. 123I-FP-CIT SPECT was useful to identify dopaminergic dysfunction and initiate dopamine replacement therapy.